Neurocognitive Development and Predictors of L1 and L2 Literacy Skills in Dyslexia: A Longitudinal Study of Children 5–11 Years Old. (29th October 2015) - Helland, Turid; Morken, Frøydis
Abstract : The aim of this study was to find valid neurocognitive precursors of literacy development in first language (L1, Norwegian) and second language (L2, English) in a group of children during their Pre‐literacy, Emergent Literacy and Literacy stages, by comparing children with dyslexia and a typical group. Children who were 5 years old at project start were followed until the age of 11, when dyslexia was identified and data could be analysed in retrospect. The children's neurocognitive pattern changed both by literacy stage and domain. Visuo‐spatial recall and RAN appeared as early precursors of L1 literacy, while phonological awareness appeared as early precursor of L2 English. Verbal long term memory was associated with both L1 and L2 skills in the Literacy stage. Significant group differences seen in the Pre‐literacy and Emergent literacy stages decreased in the Literacy stage. The developmental variations by stage and domain may explain some of the inconsistencies seen in dyslexia research. Early identification and training are essential to avoid academic failure, and our data show that visuo‐spatial memory and RAN could be suitable early markers in transparent orthographies like Norwegian. Phonological awareness was here seen as an early precursor of L2 English, but not of L1 Norwegian. © 2015 The Authors. Dyslexia published by John Wiley & Sons Ltd.